An Apprenticeship in Failure: Self-Cultivation and the Question of What to Do With Our Desires - Saari, Antti; Varpanen, Jan (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
Taking Marcel Proust’s In Search of Lost Time (À la recherche du temps perdu) as a literary vehicle, this article uses a psychoanalytic lens to examine the problem of what to do with our desires in the philosophy of education. The article describes an apprenticeship, a personal process of learning in which an ethical rapport with desire can be established. Apprenticeship entails a temporal relationship called “afterwardsness” (Nachträglichkeit), in which the subject constructs the truth of its desires in hindsight. This result can only be achieved by first failing to see the possibility of attaining the object of desire and then eventually coming to understand the nature of desire in general. While others have framed the relationship between desire and education in terms of either fulfilling one’s desires or questioning their desirability, we argue that a more lasting ethical attunement to desire can be found via an apprenticeship in failure.